Analysis of the Effect of Leadership and Organizational Culture on Employee Job Satisfaction of PT. Pos Indonesia Lubuk Pakam - Muhammad Candra (Junal Ilmu Manajemen, 2019)
The population used in this study were employees of PT. Pos Indonesia Lubuk Pakam. The method used in this sampling is the census method, with a sample of 30 people. Whereas primary data collection was carried out using the questionnaire method, which was given to the employees of PT. Pos Indonesia Lubuk Pakam. While secondary data collection is done by the method of documentation and interviews with employees of PT. Pos Indonesia Lubuk Pakam. Data analysis method used is multiple regression analysis, using SPSS program assistance. From the results of the analysis, it was found that based on the analysis of the questionnaire distributed to 30 respondents, a coefficient of determination (R Square) value of 0.951 was obtained, which means that 95% of job satisfaction was influenced by leadership and organizational culture. While 5% is influenced by other variables outside the variables examined in this study. There is a significant simultaneous effect between organizational culture leadership variables with employee job satisfaction. Based on partial testing the organizational culture leadership variable there is a significant influence on job satisfaction at PT. Pos Indonesia Lubuk Pakam.